Patients with non-small-cell lung cancer harbouring a BRAF mutation: a multicentre study exploring clinical characteristics, management, and outcomes in a real-life setting: EXPLORE GFPC 02-14 - Auliac, J.B. (Curr Oncol, 2018)
BACKGROUND: Mutations in BRAF are rare oncogene mutations, found in 2% of non-small-cell lung cancers (nsclcs). Little information is available about the management of patients with BRAF-mutated nsclc, except for those included in clinical trials. We undertook the present study to assess the clinical characteristics, management, and outcomes of those patients in a real-life setting. METHODS: This retrospective multicentre observational study included all patients with BRAF-mutated nsclc diagnosed between January 2012 and December 2014. RESULTS: Patients (n = 59) from 24 centres were included: 57.6% men; mean age: 64.5 ± 14.5 years; 82% with a performance status of 0–1 at diagnosis; smoking status: 40.3% current, 32.6% former; 93% with adenocarcinoma histology; 75% stage iv; 78% with V600E mutations; 2 with EGFR and 2 with ALK co-mutations. Of the stage iv patients, 79% received first-line therapy (14.2% anti-BRAF), and 48% received second-line treatment (23.8% anti-BRAF). Response rate and progression-free survival were, respectively, 51.7% and 8.7 months [95% confidence interval (ci): 6.4 months to 15.2 months] for first-line therapy and 35.3% and 4.1 months (95% ci: 2 months to 10.9 months) for second-line treatments. The 2-year overall survival was 58.5% (95% ci: 45.8% to 74.8%). Outcomes in patients with stage iv nsclc harbouring BRAF V600E mutations (n = 32) did not differ significantly from those of patients with other BRAF mutations. CONCLUSIONS: In this real-world analysis, most nsclc patients with a BRAF mutation were men and current or former smokers. Survival appears to be better in these BRAF-mutated patients than in nsclc patients without an oncogenic driver.